Standard terminologies for photoplethysmogram signals - Elgendi, Mohamed (2013)
Photoplethysmography is one of the optical techniques has been developed for experimental use in vascular disease. It has several advantages over other traditional experimental approaches. Because of its non-invasive, safe, costeffective and easy-to-use properties, it is considered as a useful diagnostic tool. The further developments in the Photoplethysmograph may replace it among other tools used in the assessment of vascular diseases such as blood test and ultrasound. This overview discusses the different terminologies used for the photoplethysmograph and reveals the research discontinuity among different disciplines. Moreover, it suggests standard terminologies as a resolution for a confusion persisted for more than 50 years.